2018
DOI: 10.1177/1065912918794906
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Supreme Court: How Decisions and Negativity Bias Affect Legitimacy

Abstract: While the Supreme Court’s legitimacy is generally considered essential to its influence, scholars continue to debate whether the Court’s decisions affect individuals’ assessments of it. The last week of the 2013 term provides an unusual opportunity to evaluate these issues because the Court made a conservative decision concerning the Voting Rights Act (VRA) only one day before it made a liberal one about same-sex marriage. We use original panel data of individuals’ views throughout this period, including a wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…The 2015 Angus Reid survey, which probed respondents’ views on a series of SCC decisions, shows that Conservative supporters were less likely to support these decisions at a time when Conservative supporters were also less likely to support the courts in comparison with their partisan counterparts. Research on US courts employing a policy-based framework has identified a significant relationship between support of a court’s decision and general support for the court (Bartels and Johnston 2020; Christenson and Glick 2015; 2019). Future research on Canadian courts would be well served by investigating this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 Angus Reid survey, which probed respondents’ views on a series of SCC decisions, shows that Conservative supporters were less likely to support these decisions at a time when Conservative supporters were also less likely to support the courts in comparison with their partisan counterparts. Research on US courts employing a policy-based framework has identified a significant relationship between support of a court’s decision and general support for the court (Bartels and Johnston 2020; Christenson and Glick 2015; 2019). Future research on Canadian courts would be well served by investigating this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Second, opinions of the court and nominees appear to be sufficiently partisan. Indeed, a growing literature demonstrates that the public's opinions of the court and preferences for nominees are shaped by partisan, ideological, and policy agreement (Gimpel and Wolpert, 1996; Bartels and Johnston, 2012; Christenson and Glick, 2015, 2019; Badas, 2016, 2019a,2019b; Sen, 2017). Moreover, partisan fighting and elite rhetoric further polarize these types of opinions (Rogowski and Stone, 2019).…”
Section: The Supreme Court As An Electoral Issuementioning
confidence: 99%
“…While positivity bias typically dominates these evaluations (Gibson and Caldeira 2009a), the experimental work referenced above—and Zilis (2018), in particular—highlights that group attachments play a role in spite of positivity bias. Moreover, negative sentiment often outweighs positive (Christenson and Glick 2019), and recent evidence suggests that attachments to non-judicial stimuli can trump attachment to the judiciary (Armaly, forthcoming).…”
Section: Affective Attachments Polarization and Court Supportmentioning
confidence: 99%